Assessing the Benefits and Ethical Risks of Genomic Medicine in Personalized Public Health Care - Yusriani, Yusriani; Sari, Dinda; Mustika, Puput (Journal of Asian-african Focus in Health, 2024)
Genomic medicine which leverages the insights gained from the human genome, holds transformative potential in public health by enabling personalized treatment strategies, improving disease prevention, and enhancing healthcare outcomes. This literature review examines both the benefits and risks associated with the application of genomic medicine in public health. The benefits include more accurate disease diagnoses through genetic profiling, targeted therapies for conditions like cancer and cardiovascular diseases, and improved preventive care by identifying genetic predispositions to various health conditions. These advances offer the potential for better health outcomes and cost-effective care through early interventions. However, the integration of genomic medicine into public health systems presents several risks, including ethical concerns related to privacy, genetic discrimination, and the protection of sensitive genetic data. The economic challenges associated with the implementation of genomic medicine, such as high costs and potential inequities in access, are also discussed. Additionally, the scientific uncertainty surrounding the interpretation of certain genetic variations poses challenges in clinical applications. This review highlights the need for strong policies and ethical frameworks to ensure the responsible use of genomic data while promoting equitable access to genomic technologies across diverse populations. In conclusion, while genomic medicine holds significant promise, its integration into public health systems requires careful consideration of these risks to maximize its benefits and ensure fairness in access.